PENTINGNYA PENGETAHUAN KEAMANAN PANGAN BAGI WALI MURID KB DAN TK NDASARIBUDI, KRAPYAK KULON PANGGUNGHARJO - Eni Kartika Sari; Rini Sulistyawati (LPPM IST AKPRIND Yogyakarta, 2019)
This Community Service Program aims to increase public awareness, especially KB / TK Ndasaribudi’s student parent about the importance of food safety knowledge for them. The method used is socialization, training and accompaniment. The socialization was conducted to provide a deep understanding of the types of food that are safe for consumption. Borax test training on meatballs is given so that the parents of students know the simple way to check borax in a food. The training runs well.. Based on the results of borax tests on three meatballs samples, it was found that two negative samples and one react positive in borax. So that the parents of KB / TK Ndasaribudi students are advised to provide understanding to their sons and daughters in choosing snacks to consume. In addition, based on the accompaniment carried out, it is known that the implementation of PKM has succeeded in providing education to the parents of KB / TK Ndasaribudi students marked by positive behavior changes in choosing safe foods.